2009
DOI: 10.1002/joc.1949
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of monsoon precipitation systems in and around Bangladesh

Abstract: Characteristics of precipitation systems in and around Bangladesh are analysed using 6 years of radar data from the Bangladesh Meteorological Department (BMD). Precipitation systems are classified as arc, line, or scattered types according to their shape; then as small, medium, or large according to their length; and as stationary, slow, or fast according to their propagation speed. Arc-, line-, and scattered-type systems are found 230 (29%), 117 (15%), and 442 (56%) times, respectively, from April to Septembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 26 publications
5
44
0
Order By: Relevance
“…It is of interest to see the diurnal characteristics over other regions. Rafiuddin et al [2009] analyzed premonsoon and monsoon precipitation systems around Bangladesh. They suggested that in the mature monsoon season, the precipitation systems are many, but small.…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest to see the diurnal characteristics over other regions. Rafiuddin et al [2009] analyzed premonsoon and monsoon precipitation systems around Bangladesh. They suggested that in the mature monsoon season, the precipitation systems are many, but small.…”
Section: Discussionmentioning
confidence: 99%
“…A deeper understanding of the characteristics and distribution of rainfall patterns will support water management, agricultural development and disaster management and planning in Bangladesh in the context of global climate change [4,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous efforts (e.g., [12,17,18]) have been undertaken to investigate the characteristics of rainfall patterns in Bangladesh. These studies have largely focused on either monsoon or pre-monsoon rainfall characteristics and trends.…”
Section: Introductionmentioning
confidence: 99%
“…A precise understanding of the distribution and nature of precipitation is especially useful for disaster prevention and water management in a country like Bangladesh (Rafiuddin et al, 2010). Though many studies have been carried out on rainfall and temperature in general, research on the intensity and distribution of rainfall has hardly been done for this region (Iskander et al, 2014); most research has been done on an annual or six-month basis.…”
Section: Introductionmentioning
confidence: 99%